The Role of Head Teacher Leadership in School Management - Shrestha, Sita Kumari; Subedi, Kusum Raj (Bharatpur Pragya: Journal of Multidisciplinary Studies, 2026)
This research paper examines The Role of Head Teacher leadership in School management, focusing on identifying the current status of school management and solutions to challenges faced by head teachers. The study employed a mixed-methods approach (qualitative and quantitative) and was conducted in 15 secondary community schools within Ratnanagar Municipality, Chitwan District. Participants included 60 purposively selected teachers and 15 school management committee chairpersons, totaling 108 respondents. Data were gathered from both primary and secondary sources using questionnaires, focus group discussions, direct observations, and interviews, and analyzed in relation to established theories and literature. Findings revealed that all schools prepared annual work calendars, but annual work plans, unit plans, and daily lesson plans were only partially implemented. Daily schedules often failed to balance workload and teaching responsibilities, indicating weak planning practices. Head teachers faced difficulties in managing educational activities due to issues such as lack of discipline, political interference, strikes, financial constraints, inadequate training, and poor stakeholder coordination.In terms of physical resources, half of the head teachers had successfully mobilized resources to improve facilities, one-quarter were in the process of improvement, and one-quarter showed little interest. Academically, two-thirds of head teachers made significant efforts to improve educational quality, some made minimal efforts, and a few showed little concern. Organizationally, three-fourths contributed notably to institutional strengthening. Financially, three fourths supplemented government grants with funds from organizations, donors, and agencies, while some relied solely on state funding. The study concludes that head teachers play a vital role in effective school management and should be skilled administrators, approachable, and community oriented. Recommendations include preparing and implementing annual work plans, encouraging teachers to create and follow academic plans, maintaining stakeholder coordination, and promoting extracurricular activities to enhance overall school performance.